Serum Changes in Dogs Experimentally Infected with Single Trypanosoma Congolense, Trypanosoma brucei and Conjunct Trypanosoma congolense and Ancylostoma caninum Infections and treated with Diminazene aceturate and Mebendazole - I. O., Nwoha R.; B. M., Anene (International Journal For Research In Health Sciences And Nursing, 2016)
Trypanosoma brucei (T. brucei) and Trypanosoma congolense (T. congolense) are two species of trypanosomes that pose a serious threat to the health of animals especially dogs in Nigeria. These species are often in mixed infection with Ancylostoma caninum (A. caninum). This prompted the study of serum changes in dogs experimentally infected with single T. congolense, T. brucei and conjunct T. congolense and A. caninum infections and treatment with diminazene aceturate and mebendazole. Twenty four mongrels of both sexes were randomly grouped into six of 4 members and used in the study. Group I was the uninfected control, Group II was infected with A. caninum, Group III was infected with T. congolense, Group IV was conjunct infection of T. congolense/A.caninum, Group V was infected with T. brucei, and Group VI was conjunct infection of T. brucei/A. caninum. First A. caninum infection was done on GPII, GPIV and GPVI. Two weeks later T. brucei and T. congolense were done on GPIII/GPIV and GPV/GPVI respectively. Treatment with 7 mg/kg diminazene aceturate stat and 100mg mebendazole given twice daily for 3 days was done on all the infected groups (GPIII, GPIV, GPV and GPVI). Results show significant increases (p<0.05) in blood urea nitrogen (BUN), creatinine, alanine aminotransferase (ALT), alkaline phosphatase (ALP) and aspartate aminotransferase (AST) of all the infected groups (GPII, GPIII, GPIV, GPV and GPVI). Treatment did not improve the altered serum analytes. A significant decrease (p<0.05) in blood sugar was observed only in the trypanosome infected groups (GPIII, GPIV, GPV and GPVI). It therefore show that both trypanosome species and Ancylostoma caninum cause significant damage to the kidney and liver tissues which was not resolved with treatment. The effect was more severe in combined infection of these parasites in dogs. Hence conceited effort should be enforced in prevention of occurrence of mixed infection of trypanosome/A. caninum in dogs.